Pengaruh Kecerdasan Emosional Dan Kemampuan Adaptasi Terhadap Engagement Pekerja: (Studi Kasus Pada Pekerja Non Manajer Pada Hotel Horison Palma Pangandaran ) - Nissa Laila Amri (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This research was conducted with the aim of knowing the effect of emotional intelligence and adaptability on employee engagement at Horison Palma Pangandaran Hotel. The method used in this study is a survey method using data obtained directly through questionnaires distributed to 47 respondents who are non-manager employees at Hotel Horison Palma Pangandaran. The technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that Emotional Intelligence and Adaptability simultaneously have a significant effect on Employee Engagement, Emotional Intelligence partially has a significant effect on Employee Engagement, and Adaptability Ability partially has no significant effect on Employee Engagement at Horison Palma Pangandaran Hotel.